Pengaruh Era Digital Terhadap Pemakaian Bahasa Indonesia di Kalangan Remaja Melalui Media Sosial - Parlindungan Siahaan, Andika; Aldy Pradana, Muhammad; Citra Chairani, Dwi; Heriyani Erizal, Azizah; Margareta Lase, Yuyun (Teewan Journal Solutions, 2025)
This study aims to examine the impact of the digital era on the use of the Indonesian language among teenagers, particularly through social media. With the advancement of information technology and the increasing dominance of social media platforms such as Instagram, TikTok, Twitter, and WhatsApp, the way teenagers communicate has significantly shifted. The results indicate that about 70% of teenagers frequently use informal language and slang, while only 10% maintain the use of formal language. The phenomenon of code-switching also emerged, with 25% of teenagers mixing Indonesian with foreign languages, primarily English, in their interactions. While the use of slang enriches vocabulary, the main challenge is the declining ability to communicate formally. This research emphasizes the importance of developing responsive curricula and enhancing digital literacy to balance linguistic creativity with the preservation of formal language standards.